Validación del instrumento para la evaluación del índice del potencial interpretativo. - Loachamín Proaño, Diana Estefania (2023)
The objective of this research project was to identify the methodologies proposed by different authors for the evaluation of the interpretative potential of natural and cultural resources through a bibliographic review comparing their use, application and results. For which a bibliographical review was carried out regarding the subject where documents with perceptions of different authors were found in which the criteria and their respective evaluations were analyzed. In the second objective, a data collection instrument was designed on the interpretive potential index based on the Morales and Lozano methodology, as a result, a complete file was obtained that contains three important axes such as the identification of the resource that includes seven questions according to the information of the patrimonial resource, the interpretative condition that covers the nine criteria with their respective scores and the characterization of the resource based on the description. For the third objective, the instrument was first validated by adapting the methodology of the author Supo, where specialists were selected according to their degree of knowledge on the subject and by means of a rating rubric within a Likert scale that served as a form of evaluation. question the level of agreement or disagreement with the design by the experts. Once the instrument was validated, a pilot test was applied with the final record in two sites in the Latacunga canton, Cotopaxi province, such as El Morro hill and the El Boliche National Recreation Area, where the index of interpretive potential was evaluated through a field trip. 10 resources were identified from each site, the flora and fauna that stand out the most in El Boliche as the páramo wolf and the moss with an IPI of 0.71 and in the El Morro hill with a high IPI of 0.75 for the area. rocky, these being the resources that obtained the highest score within the two sites visited.